Pengaruh Job Crafting terhadap Work Engagement pada Dosen - Resdika Januardi Aziz; Hendro Prakoso (Bandung Conference Series: Psychology Science, 2023)
Abstract. Job crafting is a form of change made on one's own initiative as an effort to improve job resources. Through job crafting efforts, work engagement can increase so that it can produce good work performance. The aim of this study is to determined the influences of job crafting on lecturer’s work engagement. The research method used is the causality method with a total of 95 lecturers at the Islamic University of Bandung (UNISBA), Pasundan University (UNPAS), and the Indonesian University of Education (UPI). This study used a job crafting scale (JCS) measuring instrument from Tims, Bakker & Derks adapted by Sutisna et al., (2020) and a measuring instrument utrechts work engagement scale-17 (UWES-17) from Schaufeli & Bakker adapted by Sutisna et al., (2020). The results of the study found that 94.7% of lecturers had high job crafting and 98.9% of lecturers had high work engagement. The effect of job crafting on work engagement in this study was 50.4%. The results of multiple regression dimensions of increasing structural job resources and increasing social job resources have the highest significant influence on work engangement. Abstrak. Job crafting adalah bentuk perubahan yang dilakukan atas inisiatif sendiri sebagai upaya meningkatkan job resources. Melalui upaya job crafting, work engagement dapat meningkat sehingga dapat menghasilkan performance kerja yang baik. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh job crafting terhadap work engagement pada dosen. Metode penelitian yang digunakan adalah metode kausalitas dengan jumlah subjek 95 dosen di Universitas Islam Bandung (UNISBA), Universitas Pasundan (UNPAS), dan Universitas Pendidikan Indonesia (UPI). Penelitian ini menggunakan alat ukur job crafting scale (JCS) dari Tims, Bakker & Derks yang diadaptasi oleh Sutisna et al., (2020) dan alat ukur utrechts work engagement scale-17 (UWES-17) dari Schaufeli & Bakker yang diadaptasi oleh Sutisna et al., (2020). Hasil penelitian ditemukan 94,7% dosen memiliki job crafting yang tinggi dan 98,9% dosen memiliki work engagement yang tinggi. Pengaruh job crafting terhadap work engagement pada penelitian ini sebesar 50,4%. Hasil multiple regression dimensi increasing structural job resources dan increasing social job resources memiliki pengaruh signifikan paling tinggi terhadap work engangement.